Prarancangan Pabrik Fatty Alcohol Ethoxylate Dari Fatty Alcohol Dan Etilen Oksida Kapsitas 50.000 Ton/Tahun - Febriyanti, Suci Amalia, Ir.Herry Purnama, M.T., Ph.D, Kusmiyati, S.T, M.T, Ph.D (2016)
Fatty Alcohol Ethoxylate (FAE) is raw material for manufacturing surfactant that use for producing cleaning agents like detergents, shampoo, soap and household tools. Furthermore, another using of FAE is for cosmetics, textile, and pharmacy. To fulfill domestic demand and opportunity to export, FAE factory is designed with a capacity of 50.000 tons/year. This factory will be established in Cilegon City, Banten Province. Raw material for manufacturing FAE is fatty alcohol and ethylene oxide and potassium hydroxide (KOH) as catalyst. The process step is divided to 3 steps, there are activation catalyst, manufacturing product in reactor and purification product. First step, mixing fatty alcohol and KOH catalyst 0,5% weight of fatty alcohol at temperature of 180 °C in 30 minutes in the mixer. In this process, activation catalyst is happened. Second step, the solution is fed to bubble reactor and reacted with ethylene oxide at temperature of 180 °C and pressure 2 atm, this reaction is called ethoxylation. The conversion as long as manufacturing product in reactor is 84,43%. Last step, the product will be refined at distillation column, so the conversion will increase into 99,8%. From economic analysis shows the Fixed Capital Investment (FCI) of IDR 760.406.850.974; Working Capital (WC) of IDR Rp 131.019.863.192; The profit before tax is IDR 323.005.900.175, the profit after tax is IDR 242.254.425.131. Percent Return On Investment before tax = 42,37 %; Percent Return On Investment after tax = 31,78%, Pay Out Time before tax = 1,91 years; Pay Out Time after tax = 2,39 years. Break Even Point (BEP) = 40,97%; Shut Down Point (SDP) = 20,08%, Discounted Cash Flow (DCF) = 39,51%.